2019
DOI: 10.1177/0192513x19849629
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Factors, Fatherhood Beliefs, and African American Fathers’ Involvement: Building the Case for a Mediated Pathway

Abstract: Intergenerational factors have been suggested as a critical interactional context shaping African American fathers’ beliefs and parenting practices. However, relatively little attention has been given to the identification of underlying processes guiding the association between intergenerational factors and African American fathers’ involvement with their children. The current investigation builds the case for fathering role ideologies and sense of parenting competence as mediators. The sample was composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 111 publications
0
11
0
1
Order By: Relevance
“…La evidencia respecto a los beneficios directos e indirectos de la implicación paterna en el desarrollo de los hijos, y su transferencia intergeneracional (Cooper et al, 2019) fundamentan la necesidad de contar con mejores herramientas de evaluación e intervención que apoyen y orienten a los padres en el desarrollo de prácticas parentales positivas.…”
Section: Discussionunclassified
“…La evidencia respecto a los beneficios directos e indirectos de la implicación paterna en el desarrollo de los hijos, y su transferencia intergeneracional (Cooper et al, 2019) fundamentan la necesidad de contar con mejores herramientas de evaluación e intervención que apoyen y orienten a los padres en el desarrollo de prácticas parentales positivas.…”
Section: Discussionunclassified
“…Thus, fathers with higher parenting self-efficacy tend to be more involved in the parenting process. However, a study by Cooper et al (2019) revealed that a father's sense of competence could not moderate whether they will be involved in parenting or not. A positive attitude toward the importance of parenting is also a predictor of paternal involvement 574 (Pilkauskas & Schneider, 2020;Cooper et al, 2019;Adamsons & Pasley, 2016;McGill, 2014;Perry & Langley, 2013;Gaertner et al, 2007).…”
Section: Father Factorsmentioning
confidence: 98%
“…Most research on the cross-generational transmission of fathers’ parenting and involvement has relied on retrospective designs, in which fathers’ reports of the parenting they experienced as children are related to their current beliefs and behaviors. Self-report studies in the U.S. have found positive cross-generational associations, suggesting that fathers’ retrospective reports of their own fathers’ positive involvement are associated with greater involvement, more positive parenting practices, higher father-child relationship quality, and greater sense of competence (Brown et al, 2018; Cooper et al, 2019; Hofferth et al, 2012). However, a study in the U.K. found that retrospective reports of their own fathers’ parenting were not associated with fathers’ observed interactions with their 24-month-olds (Madden et al, 2015).…”
Section: Relative Parental Involvement and The Father Rolementioning
confidence: 99%